Performance, Serum Biochemical and Immunological Parameters, and Digestive Enzyme and Intestinal Barrier-Related Gene Expression of Broiler Chickens Fed Fermented Fava Bean By-Products as a Substitute for Conventional Feed - Omar, Anaam E.; Al-Khalaifah, Hanan S.; Ismail, Tamer Ahmed; Abd El-Aziz, Reda M.; El-Mandrawy, Shefaa A. M.; Shalaby, Shymaa I.; Ibrahim, Doaa (Frontiers in Veterinary Science, 2021)
Improving nutritional quality of unconventional feed ingredients as fava beans by-products can enhance their utilization by broiler chickens. Hence, the quality of fermented fava beans by-products (FFB), in addition to, growth, nutrient digestibility, expression of digestive enzymes and intestinal barrier related genes and serum biochemical and immunological parameters were evaluated in response to different levels of FFB. A total number of 500, one-day-old broiler chicks (46.00 ±0.388 g) were allocated to five groups with ten replicates each (100 chicks/treatment), the first group fed corn-soybean based diet (control diet); other four groups were fed control diet substituted with 5%, 15%, 25% and 35% fermented fava beans by-products (FFB) for 38 days. Birds fed 25 % FFB showed the maximum body weight gain (increased by 12.5% when compared with control group) and most improved feed conversion ratio. Also, birds fed FFB at the level of 15, 25 and 35% had an improved dry matter and crude protein digestibility. Moreover, birds fed FFB at the level of 25 and 35% showed a decrease of ileal pH and an increase of fiber digestibility (p<0.05). Upregulation of digestive enzyme genes (AMY2A, PNLIP and CCK) were observed in groups fed FFB. Most prominent upregulation of genes encoding for tight junction proteins (claulin-1 and occludin and junctional adhesion molecules) were observed in groups fed 25% and 35% FFB (increased by 0.66, 0.31 and 1.06 and 0.74, 0.44 and 0.92 fold, respectively). Additionally, the highest expression of enterocytes protective genes [glucagon-like peptide (GLP-2), mucin-2 (MUC-2) and fatty acid-binding protein (FABP-6)] was detected in groups fed higher levels of FFB. Substitution of corn-soybean diet with FFB had an inhibitory effect on cecal pathogenic microbes and increased beneficial microflora (Lactobacilli and Bifidobacterium) especially at higher levels. Based on our results, we concluded that the substitution of corn-soybean diet with FFB can improve the growth rate and nutrient digestibility of broiler chickens, along with improving their intestinal barrier functions and increasing numbers of beneficial microorganisms. Using of FFB at the level of 25% had a positive impact on growth performance of broiler chickens and can be applicable in poultry farms